Antibacterial and pH-Responsive Chitosan/Glutaraldehyde Film with Red Cabbage Anthocyanins for Meat Freshness Detection - Masfufah, Faza Ilya Sururim; Ngadiwiyana, Ngadiwiyana; Yassaroh, Yassaroh; Wulandari, Retno; Prasetya, Nor Basid Adiwibawa (Trends in Sciences, 2025)
This study presents the development of a biodegradable chitosan-based film responsive to pH changes, utilizing anthocyanins from red cabbage extract as a natural pH indicator. Chitosan films were prepared with varying volumes of glutaraldehyde (GA) as a cross-linking agent through a casting method, followed by coating with red cabbage extract. The chitosan/GA films exhibited color transitions within a pH range of 2 - 13, changing from purple during the initial storage to green as chicken meat spoiled, effectively indicating freshness. FE-SEM analysis revealed that GA cross-linking resulted in a denser film structure, with a reducing porosity from 10.0% (pure chitosan) to 6.7% (chitosan/GA). The incorporation of glutaraldehyde significantly enhanced the films’ tensile strength, with the optimal strength achieved at 0.5 mL GA, representing a threefold increase compared to pure chitosan. The films also demonstrated improved mechanical stability, defined as an improved resistance to deformation under applied stress, which is crucial for packaging integrity. Additionally, glutaraldehyde modified films exhibited greater hydrophilicity, as indicated by changes in contact angle, and displayed antibacterial activity, with CG0.5 exhibiting the largest inhibition zone against S. aureus (4.9 mm). Although GA incorporation slightly reduced the biodegradation rate, the films still displayed acceptable biodegradability, defined as the ability to degrade by least 60% within 5 days sufficient for short-term food packaging applications. The red cabbage extract-coated chitosan-GA films effectively monitored meat spoilage through visible color changes and demonstrated eco-friendly degradation behavior, positioning them as promising smart packaging materials for chicken meat freshness monitoring. HIGHLIGHTS A novel biodegradable chitosan-based film with pH-responsive color changes for real-time chicken freshness monitoring. First report on the integration of glutaraldehyde cross-linking and anthocyanin-based sensing in a single film system. Significant enhancement in mechanical properties, with tensile strength increased threefold due to optimized cross-linking. Improved antibacterial performance, with CG0.5 exhibiting a 4.9 mm inhibition zone against aureus, enhancing food safety. GRAPHICAL ABSTRACT